FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN BAYI BERAT LAHIR RENDAH (BBLR) DI RSUD GUNUNG JATI KOTA CIREBON - Lia Yulianti (Jurnal Ilmiah Kesehatan, 2021)
Background: In Indonesia, infant deaths due to BBLR case is categorized high. According to Rikesdas result in 2013, the highest percentage of BBLR is in Central Sulawesi Province (16.8%) while the lowest is in North Sumatera (7.2%). In West Java, it is recorded at 11.8%. Methods: This study uses a descriptive method with a cross sectional approach. Data retrieval from hospital medical record data (Secondary). The population of this study were all babies born weighing less than 2500 grams.. The sample of this study is all the population of infants with low birth weight (total sampling), that is, 381 infants. Data analysis in this study was carried out using univariate and bivariate analysis. Results: According to the study result, it is found out that the incident of BBLR is 87.1%. Based on the results obtained by Chi Square test, there are 5 variables that are not related with the incidents of BBLR; those variables are gemelli (p=0.413), preeclampsia (p= 0.499), early membrane rupture (p=0.300), and anemia during pregnancy (p=713). And there are two related variables, age (p=0.002) and parity (p=0.000). Conclusion: From the study results, it is expected that the study is able to perform early detection of the incident of BBLR detect and to be used as suggestion for related institution to concentrate more in delivering information on factors and risks that may happen in BBLR. It is also expected that there will be further varied research with different methods.